2016
DOI: 10.5367/te.2016.0558
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the impact of Turkish TV series on inbound tourists

Abstract: Turkey has earned outstanding success in exporting TV series. It is believed that one of the most important results of exporting TV series is to have impact on the increment of the travel demand to Turkey, which is known as film-induced tourism effect. This field emerging recently deals with investigating the impact of TV series and movies on tourism demand. In this article, using Chow analysis whether to influence or not the citizens of Saudis and Bulgarians as visitors to Turkey is examined. It is concluded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…The growing popularity of Turkish soap operas, both historical and contemporary, proves the interest of the Croatian population in Turkey. In this regard, research findings support the conclusions made by Bolan et al (2011) and Kantarci et al (2017) about the necessity of closer collaboration and joint strategic approach of the tourism and film industries for destination (in this case Turkey) image building. The findings that negative perceptions are primarily related to human rights and gender inequality might (with caution) be interpreted as a result of cultural differences between the countries and of long-held stereotypes about conservative female dependence on male family members.…”
Section: Discussionsupporting
confidence: 82%
“…The growing popularity of Turkish soap operas, both historical and contemporary, proves the interest of the Croatian population in Turkey. In this regard, research findings support the conclusions made by Bolan et al (2011) and Kantarci et al (2017) about the necessity of closer collaboration and joint strategic approach of the tourism and film industries for destination (in this case Turkey) image building. The findings that negative perceptions are primarily related to human rights and gender inequality might (with caution) be interpreted as a result of cultural differences between the countries and of long-held stereotypes about conservative female dependence on male family members.…”
Section: Discussionsupporting
confidence: 82%
“…Finally, this study explores the internal mechanism of film-induced tourism. This study found that in previous research on film and television tourism, scholars had discussed the mechanism of film-induced tourism from identity conversion ( Kantarci et al, 2017 ; Du et al, 2020 ), motivation transfer ( Rittichainuwat and Rattanaphinanchai, 2015 ; Hetland et al, 2016 ; Oviedo-García et al, 2016 ), and demand change ( Kim and Kim, 2018 ; Qiang et al, 2019 ; Teng, 2021 ), however, the research mostly stayed at the basic stage and did not deeply explore its internal mechanism. This study has introduced “empathy” as the medium in which the mechanism occurs and has profoundly expounded that “empathy” as a medium can promote the audience-to-tourist identity change, film watching-to-traveling motivation transfer, and interest-to-expectation demand change, providing profound insights into the development of film and television tourism.…”
Section: Research Conclusionmentioning
confidence: 80%
“…This dimension distinguishes this study from other food experience studies. According to Kantarci et al (2017), TV series increase curiosity about a culture and travel motivation toward the destination of that culture. For example, the Magnificent Century is one of the most popular Turkish TV series and has been exported to over 70 countries.…”
Section: Discussion and Conclusion Conclusionmentioning
confidence: 99%